Thermoplastic composition for metal plating
A thermoplastic composition with specific polymers and surface treatment methods enables effective metal electroplating on polymer substrates without hexavalent chromium, achieving strong adhesion and impact resistance in metal-plated parts.
Patent Information
- Application Number
- CN202380039547.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-02
- Filing Date
- 2023-11-30
- Publication Date
- 2024-12-20
AI Technical Summary
The use of hexavalent chromium compounds for chemically treating polymer substrates to enhance metal adhesion in electroplating poses health risks, environmental hazards, and structural damage, while alternative methods like dry plasma etching and potassium permanganate solutions are limited in applicability and efficiency.
A thermoplastic composition comprising a first copolymer, rubber-modified polymer, and styrene maleic anhydride (SMA) copolymer, which enhances surface polarity and adhesion, allowing metal electroplating without hexavalent chromium, using a chemical agent like manganese oxide in mineral acid mixtures for surface treatment.
The composition achieves high peel strength and impact resistance in metal-plated parts, avoiding the drawbacks of traditional etching processes, with improved adhesion and mechanical properties.
Smart Images

Figure CN119173577A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority and filing date of European Patent Application No. 22211168.4 filed on December 02, 2022, which is incorporated herein by reference in its entirety. Technical Field
[0003] The present disclosure relates to thermoplastic compositions for metal electroplating and methods of metal electroplating thermoplastic compositions. Background Art
[0004] Polymer plastic parts made from thermoplastic compositions, such as acrylonitrile-butadiene-styrene (ABS) polymers, are often metallized when used in certain applications, such as automotive applications. The thermoplastic composition can serve as a polymer substrate onto which a metal coating can be deposited. For example, a polymer plastic part made from ABS polymer can be coated with a metal layer to give it a mirror-like appearance similar to a metal part while retaining the unique advantage of being lightweight. In addition, the metal coating can improve the mechanical strength, thermal stability, and chemical resistance of the underlying polymer substrate to which the metal is coated. In this regard, ABS polymers are particularly suitable for automotive and other industrial applications due to their desirable impact resistance and other useful properties.
[0005] However, there are some problems with the use of metal coatings on polymer plastic parts. Metal coatings do not easily adhere or stick to most polymer substrates unless the surface of such polymer substrates is first chemically treated. Traditionally, the surface of the polymer substrate can be chemically etched using oxidants such as hexavalent chromium trioxide or mixtures of chromic acid / sulfuric acid or chromic acid / sulfuric acid / phosphoric acid. These strong oxidants can micro-roughen and chemically change the surface of the polymer substrate by forming polar organics. The surface of the substrate has functional groups such as R-COOH, R-OH, R-SO3, R-CH=O. The presence of these polar groups can promote the adsorption of electroplating catalysts from aqueous solutions, thereby allowing subsequent metal deposition to occur during the electroplating process. After the etching process, the surface of the polymer substrate can be metal plated. A suitable indicator of the degree of successful bonding between the metal layer and the polymer substrate is the peel strength. The greater the peel strength, the better the adhesion of the metal on the polymer substrate.
[0006] However, the use of hexavalent chromium compounds such as chromium trioxide presents certain risks and challenges, such as (1) health risks, as such compounds are carcinogenic, (2) effective treatment of wastewater generated by the etching process, which makes such etching processes not only environmentally harmful but also costly, (3) purification of the etched plastic parts to remove any residual chromium trioxide that may be present in the form of impurities, as such impurities can adversely affect the metal electroplating process, and / or (4) the use of highly oxidizing acid solutions that often damage the polymer substrate itself or make its structure fragile and unfavorable for metal electroplating.
[0007] To avoid these problems, many alternative processes to chromic acid etching have been investigated. For example, dry plasma etching has been proposed as an alternative to wet etching. However, the application of this method is limited to flat polymer parts. Alternatively, attempts have been made to use etchants such as potassium permanganate instead of chromic acid. Although the use of heated alkaline permanganate solutions has achieved some limited commercial success, the applicability of permanganate solutions is mostly limited due to their slower oxidation rate than chromic acid. From a commercial perspective, it is desirable to obtain the strongest possible bond between the surface of the thermoplastic article and the electroless metal deposited thereon so that electroplating can be easily performed.
[0008] Exemplary embodiments of the present disclosure relate to thermoplastic compositions for metal electroplating. The thermoplastic composition includes a first copolymer in an amount of 30% to 80% by weight of the composition. The first copolymer includes polymer units derived from vinyl aromatic monomers and vinyl nitrile monomers. The thermoplastic composition also includes a rubber-modified polymer accounting for 18%-50% by weight of the composition and a styrene maleic anhydride (SMA) copolymer accounting for 2%-15% by weight of the composition. The SMA copolymer includes a maleic anhydride content of 10%-30% by weight of the SMA copolymer, and the weight average molecular weight of the SMA copolymer is 5,000 g / mol to 30,000 g / mol.
[0009] In some embodiments, the vinyl aromatic monomer includes at least one of styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene and methoxystyrene (preferably, the vinyl aromatic monomer is styrene), and the vinyl nitrile monomer includes at least one of acrylonitrile, chloroacrylonitrile, methacrylonitrile and ethacrylonitrile (preferably, the vinyl nitrile monomer is acrylonitrile).
[0010] In some embodiments, the rubber modified polymer includes a polymer rubber having polymer units derived from a conjugated diene, and the rubber modified polymer further includes a grafted thermoplastic copolymer grafted onto the polymer rubber.
[0011] In some embodiments, the rubber modified polymer includes a polymer rubber having polymer units derived from conjugated dienes. The conjugated dienes include at least one of 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene and 2,4-hexadiene (preferably 1,3-butadiene). The rubber modified polymer also includes a grafted thermoplastic copolymer grafted onto the polymer rubber. The grafted thermoplastic copolymer includes polymer units derived from a vinyl aromatic monomer (preferably styrene) and a vinyl nitrile monomer (preferably acrylonitrile).
[0012] In some embodiments, the first copolymer comprises styrene-acrylonitrile copolymer (SAN) and the rubber modified polymer comprises SAN grafted butadiene rubber.
[0013] In some embodiments, the thermoplastic composition further comprises 2% to 10% by weight of ethylene acrylic acid (EAA) copolymer. The content of acrylic acid in the EAA copolymer is 1%-10% by weight of the EAA copolymer, preferably 5%-7% by weight of the EAA copolymer.
[0014] In some embodiments, the thermoplastic composition comprises one or more additional components in an amount of 0% to 5% by weight of the composition.
[0015] In some embodiments, the one or more additional components in the thermoplastic composition are selected from impact modifiers, flow modifiers, reinforcing agents, antioxidants, heat stabilizers, light stabilizers, UV stabilizers, UV absorbing additives, plasticizers, lubricants, mold release agents, antistatic agents, melt processing additives, and any combination thereof.
[0016] In some embodiments, the one or more additional components include at least one of magnesium oxide (MgO), silicone oil, ethylene bisstearamide (EBX) wax, and magnesium stearate.
[0017] In some embodiments, the thermoplastic composition has a notched Izod impact strength of 3.0 kJ / m when measured according to ISO 180 / 1A. 2 Up to 30.0kJ / m 2 , preferably 4.0 kJ / m 2 Up to 25.0kJ / m 2 , more preferably 5.0 kJ / m 2 Up to 20.0kJ / m 2 .
[0018] Various embodiments of the present disclosure are directed to an electroplating process that includes molding a thermoplastic composition to form a molded part, followed by depositing a metal on the molded part to produce a metal-plated molded part having high peel strength and good impact properties. The method includes: (i) molding the thermoplastic composition into a molded article; (ii) optionally cleaning and / or rinsing the molded article; (iii) contacting the surface of the molded article with a chemical agent to form a surface-treated article; and (iv) subjecting the surface-treated article to conditions suitable for adhering one or more metal layers to at least a portion of the surface of the surface-treated article to produce a metal-plated article.
[0019] In some embodiments, the chemical agent includes a suspension of colloidal particles of manganese oxide in a mineral acid mixture comprising sulfuric acid and / or phosphoric acid.
[0020] In some embodiments, the one or more metal layers are selected from the group consisting of copper, nickel, and chromium (preferably nickel).
[0021] In some embodiments, the metal-coated article has a peel strength greater than 0.4 N / mm as measured according to ASTM B533-85.
[0022] Further embodiments of the present disclosure are directed to a thermoplastic composition for use in preparing metal-coated articles suitable for use in various industrial applications requiring materials with excellent impact strength. In addition, in one aspect, the thermoplastic composition of the present disclosure can be coated with metal without using a chemical etching process that relies on an oxidizing agent (e.g., hexavalent chromium trioxide or a mixture of chromic acid / sulfuric acid or chromic acid / sulfuric acid / phosphoric acid).
[0023] Exemplary embodiments of the present disclosure also relate to metal-plated articles comprising a metal layer and a thermoplastic article. The metal layer is adhered to at least a portion of the surface of the thermoplastic article. The thermoplastic article includes a copolymer accounting for 30% to 80% of the weight of the composition. The copolymer includes polymer units derived from vinyl aromatic monomers and vinyl nitrile monomers. The thermoplastic composition also includes a rubber-modified polymer accounting for 18%-50% of the weight of the composition and a styrene maleic anhydride (SMA) copolymer accounting for 2%-15% of the weight of the composition. The maleic anhydride content in the SMA copolymer is 10%-30% by weight, and the SMA copolymer and the SMA copolymer include a weight average molecular weight of 5,000g / mol to 30,000g / mol.
[0024] In some embodiments, the metal-coated article is an automotive or electrical part. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and other features, aspects and advantages of the present disclosure will be better understood when the following detailed description of the present disclosure is read with reference to the accompanying drawings, in which:
[0026] 1 shows a graph of peel force (in N / mm) versus peel length (in mm) for Examples E2 and E6 and Comparative Example CE1 according to various embodiments of the present disclosure. DETAILED DESCRIPTION
[0027] Exemplary embodiments of the present disclosure relate to thermoplastic compositions. The thermoplastic composition includes a first copolymer accounting for 30% to 80% by weight of the composition. The copolymer includes polymer units derived from vinyl aromatic monomers and vinyl nitrile monomers. The thermoplastic composition also includes a rubber modified polymer accounting for 18%-50% by weight of the composition and a styrene maleic anhydride (SMA) copolymer accounting for 2%-15% by weight of the composition. The SMA copolymer includes a maleic anhydride content accounting for 10%-30% by weight of the SMA copolymer, and the weight average molecular weight of the SMA copolymer is 5,000 g / mol to 30,000 g / mol. Without being bound by theory, the inventors believe that the incorporation of SMA into ABS results in the presence of polar anchoring groups on the surface of the molded article (which includes the thermoplastic composition of the present disclosure). The presence of maleic anhydride groups in SMA increases the surface energy and surface polarity of the surface of the molded article. These increases result in better interfacial adhesion between ABS and the metal to be bonded to the surface of the molded article, thereby enabling easy metallization. The details of various embodiments are discussed below.
[0028] Thermoplastic composition The thermoplastic composition described herein includes a first copolymer, which is present in an amount of 30% to 80% by weight of the composition, preferably 45% to 75% by weight of the composition. The first copolymer comprises polymer units derived from vinyl aromatic monomers and vinyl nitrile monomers. The thermoplastic composition also includes a rubber modified polymer in an amount of 18% to 50% by weight of the composition, preferably 30% to 45% by weight of the composition. The thermoplastic composition also includes a styrene maleic anhydride (SMA) copolymer, which is present in an amount of 2% to 15% by weight of the composition. The maleic anhydride content in the SMA copolymer is 10% to 30% by weight of the SMA copolymer, preferably 12% to 25% by weight of the SMA copolymer, and more preferably 15% to 20% by weight of the SMA copolymer. The weight average molecular weight of the SMA copolymer is 5,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 25,000 g / mol, and more preferably 15,000 g / mol to 20,000 g / mol.
[0029] The thermoplastic composition can be molded or formed into a polymer article. The polymer article can have suitable impact properties necessary for certain applications, including door handles, brackets, lamp bodies, company logos, and other decorative parts used in the automotive industry, household appliances, electronic products, furniture, sanitary fittings, etc. For example, when measured according to ISO 180 / 1A, the notched Izod impact strength of the polymer article can be ≥3.0 kJ / m 2 , preferably 4.0 kJ / m 2 Up to 25.0kJ / m 2 , more preferably 5.0 kJ / m 2 Up to 20.0kJ / m 2 .
[0030] Copolymer (A)
[0031] The thermoplastic composition described herein comprises a copolymer comprising polymer units derived from a vinyl aromatic monomer and a vinyl nitrile monomer. Based on the total weight of the thermoplastic composition, the first copolymer can be present in an amount of 30% to 80% by weight of the thermoplastic composition, preferably 45% to 75% by weight of the thermoplastic composition, or any range or value therebetween.
[0032] Non-limiting examples of vinyl aromatic monomers include styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene, methoxystyrene or any combination thereof. Non-limiting examples of vinyl nitrile monomers include acrylonitrile, α-chloroacrylonitrile, methacrylonitrile, ethacrylonitrile or any combination thereof. In one embodiment, the vinyl aromatic monomer is styrene and the vinyl nitrile monomer is acrylonitrile. Preferably, the copolymer is a styrene acrylonitrile (SAN) copolymer. In a preferred aspect of the present disclosure, the copolymer can be a styrene acrylonitrile copolymer having a polymer unit derived from acrylonitrile greater than or equal to 30.0% by weight and less than or equal to 35.0% by weight.
[0033] In some aspects of the present disclosure, the copolymer can be a terpolymer comprising polymer units derived from (i) vinyl aromatic monomers, (ii) vinyl nitrile monomers and (iii) (meth) acrylic acid monomers. Vinyl aromatic monomers and vinyl nitrile monomers can be selected from monomers as defined above. Non-limiting examples of (meth) acrylic acid monomers can include methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, hexyl methacrylate and decyl methacrylate. Preferably, the (meth) acrylic acid monomer can be methyl methacrylate (MMA). Therefore, the copolymer can be a terpolymer comprising polymer units derived from styrene / acrylonitrile / methyl methacrylate or derived from α-methylstyrene / acrylonitrile / methyl methacrylate.
[0034] The copolymer may have a suitable molecular weight and melt flow rate. The weight average molecular weight (Mw) of the copolymer may be 50,000 g / mol to 100,000 g / mol or any range or value therebetween, as determined by gel permeation chromatography according to ASTM D5296-11, using polystyrene-based calibration, with tetrahydrofuran (THF) as solvent. The melt flow rate of the copolymer may be 7.0 g / 10 min to 40.0 g / 10 min or any value or range therebetween, as determined by ASTM D 1238 at 230° C. and 3.8 kg load. If the melt flow rate of the copolymer is higher than these rates, the overall impact properties of the thermoplastic composition may be adversely affected, and if the melt flow rate of the copolymer is lower than these rates, the desired flow properties of the thermoplastic polymer may not be achieved, thereby affecting the melt processability of the thermoplastic polymer.
[0035] Rubber modified polymer (B)
[0036] The thermoplastic composition described herein comprises a rubber modified polymer in an amount of 18%-50% by weight of the composition, or any range or value therebetween. The rubber modified polymer may be referred to as a high rubber graft or "HRG". The thermoplastic composition may include at least 26.0% of the rubber modified polymer. In some aspects, the thermoplastic composition may include a rubber modified polymer in an amount of 20.0% to 50.0% by weight of the total thermoplastic composition, or any range or value therebetween.
[0037] The rubber modified polymer may include a suitable amount of polymer rubber, preferably 55.0% to 75.0% by weight relative to the gross weight of the rubber modified polymer. The polymer rubber may include polymer units derived from conjugated dienes. Non-limiting examples of conjugated dienes include 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene and any combination thereof. Preferably, the conjugated diene is 1,3-butadiene, and the polymer rubber may be polybutadiene.
[0038] In a preferred aspect of the present disclosure, the rubber modified polymer comprises a polymer rubber containing polymer units derived from 1,3-butadiene and a grafted thermoplastic copolymer grafted onto the polymer rubber. The grafted thermoplastic copolymer comprises polymer units derived from a vinyl aromatic monomer (preferably styrene) and a vinyl nitrile monomer (preferably acrylonitrile). The most preferred rubber modified polymer is acrylonitrile butadiene styrene (ABS).
[0039] Styrene Maleic Anhydride Copolymer, SMA(C)
[0040] The thermoplastic composition described herein comprises a styrene maleic anhydride (SMA) copolymer in an amount of 2% to 15% by weight of the composition, preferably 5% to 20% by weight of the composition, and more preferably 10% to 15% by weight of the composition. The SMA copolymer is composed of styrene and maleic anhydride monomers. The maleic anhydride content in the SMA copolymer is 10%-30% by weight of the SMA copolymer, preferably 12%-25% by weight of the SMA copolymer, and more preferably 15%-20% by weight of the SMA copolymer. In various embodiments, the weight average molecular weight of the SMA copolymer is 5,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 25,000 g / mol, and more preferably 15,000 g / mol to 20,000 g / mol.
[0041] Generally speaking, SMA is produced by reacting maleic anhydride with styrene at high temperature in the presence of a peroxide catalyst, such as shown in U.S. Pat. No. 2,866,771, U.S. Pat. No. 2,971,939 and references cited therein. The copolymer can also be used to replace styrene, such as methyl styrene, 2,4-dimethylstyrene, chlorostyrene and other substituted styrenes. The weight average molecular weight of the SMA copolymer can vary over a wide range, for example, from about 5,000 g / mol to 30,000 g / mol, preferably from 10,000 g / mol to 25,000 g / mol, and more preferably from 15,000 g / mol to 20,000 g / mol. A representative structure of SMA is shown in FIG. 1A .
[0042] The thermoplastic composition may also include 2%-10% by weight of ethylene acrylic acid (EAA) copolymer. The EAA copolymer may include 1% to 10%, preferably 5% to 7% acrylic acid, accounting for the total weight of the EAA copolymer. The representative structure of EAA is shown in Scheme 1 (B), where x=160 to 800 and y=4.8 to 35.
[0043]
[0044] Other ingredients (D)
[0045] Depending on the application and use, the thermoplastic composition described herein may include one or more additional components. For example, the thermoplastic composition may include 0% to 5%, preferably 0% to 3%, of other components based on the total weight of the thermoplastic composition.
[0046] Non-limiting examples of one or more other components that may be used include impact modifiers, flow modifiers, reinforcing agents, antioxidants, heat stabilizers, light stabilizers, UV stabilizers, UV absorbing additives, plasticizers, lubricants, mold release agents, antistatic agents, melt processing additives, or any combination thereof. The additional component preferably comprises at least one melt processing additive.
[0047] Melt processing additives may include magnesium oxide (MgO), silicone oil, ethylene bis(stearamide) wax (EBS wax), magnesium stearate, and combinations thereof.
[0048] The melt processing additive may be included in an amount of 0% to 5%, preferably 1% to 3%, based on the total weight of the thermoplastic composition.
[0049] Thermoplastic Compositions The combination of specific types and amounts of materials constituting the thermoplastic compositions described herein produces favorable impact performance characteristics and peel strength. The embodiments and comparative examples disclosed herein provide those skilled in the art with materials within and outside the scope of the present disclosure, thereby forming a basis for developing further embodiments according to the present disclosure.
[0050] For the avoidance of doubt, it should be understood by those skilled in the art that the total weight of the composition is 100%, and any combination of materials having a total weight less than 100% is unrealistic and does not conform to the present disclosure.
[0051] According to some embodiments of the present disclosure, the thermoplastic composition is selected to have a notched Izod impact resistance of 3.0 kJ / m 2 measured at a temperature of 23° C. according to ISO 180 / 1A. 2 Up to 30.0kJ / m 2 , preferably 4.0 kJ / m 2 Up to 25.0kJ / m2 , more preferably 5.0 kJ / m 2 Up to 20.0kJ / m 2
[0052] The preferred range of the amount of the component and the preferred range of the composition property can be combined without restriction, as long as they belong to the disclosed range defined in the broadest form herein. That is, the preferred range of one or more of the amount and / or type of the components constituting the thermoplastic composition can be combined with the preferred range of one or more of the properties of the thermoplastic composition, and all such combinations are considered as disclosed herein. The composition can be manufactured by various methods known in the art. For example, the first copolymer, the rubber-modified polymer, the SMA and other additives are first mixed in a high-speed mixer or by manual mixing. Then, the mixture is fed into the throat of the twin-screw extruder through a hopper. Alternatively, at least one component can be directly fed into the extruder at the throat and / or downstream through a side feeder, or by mixing it with the desired polymer into a masterbatch and feeding it into the extruder, at least one component is incorporated into the composition. For example, a Krupp Werner & Pfleiderer ZSK2 co-rotating meshing 10-barrel twin-screw extruder with a diameter of 25 mm and an L / D ratio of 41 can be used to prepare the composition.
[0053] temperature
[0054] The temperature of the extruder along the length of the screw may be 180°C-265°C. The extrudate may be immediately cooled in a water bath and pelletized. The length of the pellets so prepared may be 0.6 cm or shorter as desired. Such pellets may be used for subsequent molding, shaping or forming. The extruded form may be subjected to suitable conditions to produce molded thermoplastic articles. For example, the thermoplastic pellets of the present disclosure may be injection molded into strips, sheets or shapes.
[0055] Electroplating process
[0056] Another subject of the present disclosure is the use of the polymer blends according to the invention for electroplating.
[0057] A further embodiment of the present disclosure is a metal-plated article comprising the thermoplastic composition of the foregoing invention. The surface of the article is at least partially or preferably completely coated with one or more metal layers (e.g., metallized). The metal-plated molded article can be obtained by conventional metal plating methods of thermoplastic compositions, such as (i) conventional electroplating methods or (ii) direct plating methods. Such methods have been previously described and are well known in the art.
[0058] The electroplating method according to the present disclosure may include the following steps:
[0059] i. molding the thermoplastic composition described herein into a molded article,
[0060] ii. optionally cleaning and / or rinsing the molded article,
[0061] iii. contacting the surface of the molded article with a chemical agent to form a surface-treated article, and
[0062] iv. subjecting the surface treated article to conditions suitable for adhering one or more metal layers to at least a portion of the surface of the surface treated article to produce a metal coated article.
[0063] In some aspects of the present disclosure, molded articles prepared from the thermoplastic compositions of the present disclosure may be surface treated.
[0064] The surface treatment may include contacting at least a portion of the thermoplastic composition (e.g., a molded thermoplastic composition) of the present disclosure with a chemical agent for a sufficient period of time (e.g., 5.0 minutes to 30.0 minutes, preferably 10.0 minutes to 20.0 minutes) to form a surface-treated thermoplastic composition. The contact temperature may range from 60°C to 80°C, preferably 65.0°C to 75.0°C. The surface-treated polymer article may have a suitable surface polarity while retaining the desired impact strength. The properties of surface polarity and impact strength may be attributed to a purposeful combination of suitable polymer articles, suitable chemical agent selection, and suitable process parameters of temperature and contact / exposure time period.
[0065] Advantageously, in some embodiments, surface treated articles can be produced without the use of hexavalent chromium compounds, thereby avoiding the disadvantages associated with conventional etching processes using hexavalent chromium compounds. The article can be contacted with the chemical agent for an appropriate time to ensure that the desired surface roughness is achieved. For example, if the article is in contact with the chemical agent for too long (e.g., greater than 30 minutes), the surface of the article may be damaged. If the article is in contact with the chemical agent for too short a time (e.g., less than 5 minutes), the surface morphology of the article will not be sufficiently changed, thereby making it impossible for the surface treated article to adhere to the metal layer. The chemical agent can be a suspension of sulfuric acid solution (70.0 volume %), manganese oxide colloidal particles suspended in a mineral acid mixture, potassium permanganate solution (6.5 volume %), or any combination thereof. In some aspects, the chemical agent can be a colloidal suspension comprising manganese oxide colloidal particles suspended in a mineral acid mixture of sulfuric acid and phosphoric acid. For example, for 1 liter of solution, the amount of manganese oxide colloidal particles present can be 50.0g / l to 70.0g / l, the amount of phosphoric acid present can be 210.0ml / l to 230.0ml / l, and the amount of sulfuric acid present can be 560.0ml / l to 580.0ml / l. The chemical reagent can include sulfuric acid (H2SO4) with a molar strength between 8.0M and 14.0M and / or phosphoric acid with a molar strength between 2.0M and 6.0M. The surface-treated products of exemplary embodiments of the present disclosure can retain favorable impact properties even after surface treatment with chemical reagents. In one aspect of the present disclosure, the surface-treated products of the present disclosure can be subjected to conditions suitable for adhering one or more metal layers to at least a portion of the treated surface to metal-plated products to form metal-plated products. Metal plating can be performed by known metal plating techniques. For example, a combination of chemical plating and electroplating can be used herein. In one aspect, the surface-treated articles can be chemically treated to produce metal plating precursor materials. The metal-plated precursor article can be contacted with a metal electrolyte solution at any applied current (e.g., >1.0 ampere and <4.0 ampere, and for a time period >5 minutes and <30 minutes) to produce a metal-plated article. The one or more metal layers are selected from the group consisting of copper, nickel, and chromium, preferably nickel. According to the present invention, at least a portion of the surface of the molded article is coated with one or more metal layers. The thickness of the single layer may be between 0.1 and 50 μm. The peel strength of the metal-plated article measured according to ASTM B533-85 may be greater than 0.4 N / mm, preferably 0.5 N / mm to 2.0 N / mm, and more preferably 0.6 N / mm to 1.5 N / mm.
[0066] In some embodiments, the metal-plated article is incorporated into a housing component of an electrical or consumer electronic device or an automotive frame or reflector. It can also be used for door handles, brackets, lamp bodies, company logos and many other decorative parts in the automotive industry, household appliances, electronics, furniture, sanitary ware and other fields. In one aspect, the metal-plated article is used in automotive applications, particularly exterior applications, such as automotive front grilles and wheel covers. The metal-plated article molded from the thermoplastic composition of the present disclosure shows improved adhesion between the metal layer and the plastic material. In addition, thermal cycle adhesion is improved and mechanical properties are excellent.
[0067] Example
[0068] The present disclosure will now be described using the following non-limiting examples to demonstrate its practice and advantages.
[0069] It should be understood that these examples are given by way of illustration only and are not intended to limit the description of the appended claims in any way.
[0070] Preparation of Thermoplastic Compositions of the Present Disclosure and Comparative Thermoplastic Compositions.
[0071] All formulations were prepared on a 4 kg scale.
[0072] The ingredients of the composition and their sources are listed in Table 1, while the details of the formulation are listed in Table 2.
[0073] Table 1: Components of the compositions and their sources.
[0074]
[0075]
[0076] The mixture of SAN granules (A) and SMA (C) was added through the main hopper / feeder, while the premix of butadiene rubber (rubber modified thermoplastic polymer (B)) and EBX wax, magnesium stearate, mixture (e.g. magnesium oxide and silicone oil) were fed through a side feeder connected to the second barrel (see Table 3). Comparative Example CE1 was prepared by mixing equal amounts of SAN1 and SAN2 (copolymer (A)) without adding any SMA. Comparative Examples CE2 and CE3 and Example thermoplastic compositions of the present disclosure (E1 to E1 1) were prepared in the same manner as the comparative samples, but before loading into the main hopper, the granules of SMA (C) and the mixture of SAN were premixed together in a plastic container to produce uniformly mixed granules. Similarly, the premix in the form of a uniform powder was obtained by dry blending HRG and melt processing additives in a separate plastic container. The content of melt processing additive (MPA) in all formulations is: MgO (0.04%), silicone oil (0.2%), EBX wax (1%), magnesium stearate (0.3%).
[0077] Table 2: Formulations of thermoplastic compositions.
[0078]
[0079] The physically mixed formulations were melt mixed in a 10 barrel Coperion ZSK-26 mm co-rotating twin screw extruder with an L / D ratio of 40: 1. The material throughput during extrusion was adjusted to maintain the specific mechanical energy (SME) between 0.172 and 0.185 while maintaining the screw speed at 250. Table 3 lists the temperature profiles used during the extrusion of the formulations of the present disclosure.
[0080] Table 3
[0081] bucket 1 2 3 4 5 6 7 8 9 10 Temperature ℃ 107 204 225 230 240 240 240 240 240 245
[0082] Test specimens such as ISO tensile bars, ISO impact bars and 3 mm color plates were injection molded using L&T Detech 100 ton molding equipment equipped with a 32 mm diameter screw. Injection molding was carried out at a temperature of 240°C and the injection speed was maintained at 20 mm / s. The molded plates were stored at 23°C and 50% relative humidity (RH) for 72 hours.
[0083] The metal plating of molded plaques of the thermoplastic composition and the thermoplastic composition of the present disclosure was compared.
[0084] Chemical plating process:
[0085] The surface of each molded plate is placed in a plating tank and subjected to chemical plating, whereby the metal ions in the plating tank are reduced and combined with the polar groups of the polymer plate to form a metal layer on the surface of the plate.
[0086] All panels (including comparative and exemplary thermoplastic compositions) were etched in a conventional manner with hexachromic acid at 70°C for 10 minutes prior to placing the panels in the plating tank.
[0087] All pretreated panels were sensitized in SnCl2 (10 g / L) / HCl (40 mL / L) solution and activated in PdCl2 (0.25 g / L) / HCl (2.5 mL / L) solution.
[0088] The electroless plating solution contained Cu SO4.5H2O (15 g / L), NaKC4H4O6.4H2O (30 g / L), HCHO (100 mL / L), and NaOH (4 g / L). All samples were electrolessly plated for 15 minutes. The sheet resistance of the coated boards was tested and electroplated using the following process.
[0089] Electroplating process:
[0090] The electrodeposition experiment included a copper deposition step and was performed using a MiniContact RS electroplating system. The electrolyte solution consisted of 75 g / L copper sulfate and 200 mL / L sulfuric acid. The applied current was 1.5 amps and the temperature was 29°C. The electroplating time for both the comparative thermoplastic composition and the exemplary thermoplastic composition of the present disclosure was 30 minutes.
[0091] The electroplating process conditions were optimized based on the applied current and treatment time. In addition, it was found that there was a statistically significant trend in the metal growth on the plates of the formulated thermoplastic composition of the present disclosure. In addition, when the treatment time was changed from 5 minutes to 30 minutes, the thickness of the metal layer grown on the surface of the plaques seemed to increase.
[0092] In order to have limited control over the metal thickness during the electroplating process, different parameters (current and time) need to be considered. In order to compare the final peel strength of different samples, a constant metal thickness is required to ensure that the difference in peel strength is mainly due to the different bonding processes (i.e. chemical bonding vs. mechanical bonding). However, in these examples, the surface conductivity of each sample is different depending on the chemical electroplating step. Therefore, all samples were cut to the same diameter to maintain the same surface area. The electroplating was performed on the same day, keeping the pH, electrolyte concentration, applied current, treatment time and temperature constant.
[0093] Peel testing of the comparative thermoplastic composition and exemplary thermoplastic compositions of the present disclosure.
[0094] Exemplary thermoplastic compositions (E1 to E11) of the present disclosure and comparative examples (CE1 to CE3) were metallized and tested for peel adhesion. FIG. 1 shows a plot of peel force (in N / mm) versus peel length (in mm) for CE, E2, and E6. The peel length and peel strength of the examples were found to be much higher than that of comparative example CE1. Table 4 shows the average peel strength as determined in accordance with ASTM B533-85. Table 4 also shows the notched Izod impact (NII) strength of molded articles prepared with the thermoplastic compositions in accordance with ISO 180 / 1A.
[0095] From the results, it can be seen that the texture provided using the thermoplastic composition of the present disclosure provides better metal-plastic interlock and good peel force compared to comparative thermoplastic compositions that do not include the specific SMA of the present disclosure.
[0096] Table 4: Average NII values and peel strength values of experimental formulations
[0097]
[0098] It should be understood that for the purpose of this disclosure, "at least one of X, Y and Z" can be interpreted as only X, only Y, only Z, or any combination of two or more of X, Y and Z (e.g., XYZ, XY, XZ, YZ). In addition, it should be understood that for the purpose of this disclosure, "X, Y and / or Z" can be interpreted as only X, only Y, only Z, or any combination of two or more of X, Y and Z (e.g., XYZ, XY, XZ, YZ). In addition, it should be understood that for the purpose of this disclosure, when numerical ranges are listed herein, upper and lower limits are included, unless otherwise specified in specific circumstances, otherwise the range is intended to include all integers and fractions within its endpoints and range. When defining a range, the scope of the present invention is not limited to the specific values described. In addition, when an amount, concentration or other value or parameter is given as a list of a range, one or more preferred ranges or higher preferred values and lower preferred values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether these pairs are disclosed separately. Although various embodiments of the disclosure have been shown and described, modifications to the various embodiments can be made without departing from the spirit and teachings of the disclosure.
[0099] The embodiments and examples described herein are exemplary only and are not intended to be limiting. The content disclosed herein may be subject to a variety of changes and modifications, all within the scope of the present disclosure. Therefore, the scope of protection is not limited by the above description, but only by the attached claims, which include all equivalents of the subject matter of the claims. Each claim is incorporated into the specification as an embodiment of the present disclosure. Therefore, the claims are further descriptions and supplement the detailed description of the present disclosure. The disclosures of all patents, patent applications, and publications cited herein are incorporated herein by reference.
Claims
1. A thermoplastic composition, characterized in that It comprises: a first copolymer in an amount of 30% to 80% by weight of the composition, preferably 45% to 75% by weight of the composition, wherein the first copolymer comprises polymer units derived from a vinyl aromatic monomer and a vinyl nitrile monomer; A rubber-modified polymer in an amount of 18% to 50% by weight of the composition, preferably 30% to 45% by weight of the composition; and 2% to 15% by weight of the composition of a styrene maleic anhydride (SMA) copolymer, The SMA copolymer contains 10% to 30% maleic anhydride by weight of the SMA copolymer, preferably 12% to 25% by weight of the SMA copolymer, and more preferably 15% to 20% by weight of the SMA copolymer. The SMA copolymer has a weight average molecular weight of 5,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 25,000 g / mol, and more preferably 15,000 g / mol to 20,000 g / mol.
2. The thermoplastic composition according to claim 1, characterized in that The vinyl aromatic monomer comprises at least one of styrene, α-methylstyrene, dibromostyrene, vinyltoluene, vinylxylene, butylstyrene, p-hydroxystyrene and methoxystyrene, preferably the vinyl aromatic monomer is styrene, and the vinyl nitrile monomer comprises at least one of acrylonitrile, chloroacrylonitrile, methacrylonitrile and ethacrylonitrile, preferably the vinyl nitrile monomer is acrylonitrile.
3. The thermoplastic composition according to claim 1 or 2, characterized in that The rubber modified polymers include: (i) a polymer rubber comprising polymer units derived from a conjugated diene, wherein the conjugated diene comprises at least one of 1,3-butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene, 1,3-hexadiene and 2,4-hexadiene, preferably 1,3-butadiene; and (ii) A grafted thermoplastic copolymer grafted onto a polymeric rubber, wherein the grafted thermoplastic copolymer comprises polymer units derived from at least one vinyl aromatic monomer, preferably styrene, and a vinyl nitrile monomer, preferably acrylonitrile.
4. Thermoplastic composition according to any one or more of claims 1 to 3, characterized in that wherein the first copolymer comprises styrene-acrylonitrile copolymer (SAN) and the rubber modified polymer comprises SAN grafted butadiene rubber.
5. Thermoplastic composition according to any one or more of claims 1 to 4, characterized in that Further including: 2% to 10% by weight of the composition of an ethylene acrylic acid (EAA) copolymer, wherein the EAA copolymer comprises an acrylic acid content of 1% to 10% by weight of the EAA copolymer, preferably 5% to 7% by weight of the EAA copolymer.
6. The thermoplastic composition according to any one of claims 1 to 6, characterized in that It also comprises: one or more other components, the amount of which is 0%-5% by weight of the composition.
7. The thermoplastic composition according to any one of claims 6, characterized in that The one or more additional components in the thermoplastic composition are selected from impact modifiers, flow modifiers, reinforcing agents, antioxidants, heat stabilizers, light stabilizers, UV stabilizers, UV absorbing additives, plasticizers, lubricants, mold release agents, antistatic agents, melt processing additives and any combination thereof.
8. The thermoplastic composition according to any one of claims 6, characterized in that The one or more additional components include at least one of magnesium oxide (MgO), silicone oil, ethylene bisstearamide (EBX) wax and magnesium stearate.
9. Thermoplastic composition according to any one or more of claims 1 to 8, characterized in that When measured according to ISO180 / 1A, its notched Izod impact strength is 3.0 kJ / m 2 Up to 30.0kJ / m 2 , preferably 4.0 kJ / m 2 Up to 25.0kJ / m 2 , more preferably 5.0 kJ / m 2 Up to 20.0kJ / m 2 .
10. An electroplating method, characterized in that: include: Forming a thermoplastic composition according to any one or more of claims 1 to 9 into a molded article; optionally cleaning and / or rinsing the molded article; contacting the surface of the molded article with a chemical agent to form a surface-treated article; and subjecting the surface treated article to conditions suitable for adhering one or more metal layers to at least a portion of the surface of the surface treated article to produce a metal coated article.
11. The electroplating method according to claim 10, characterized in that: The chemical agent comprises a suspension of colloidal manganese oxide particles in a mineral acid mixture comprising sulfuric acid and / or phosphoric acid.
12. The electroplating method according to claim 10 or 11, characterized in that: The one or more metal layers are selected from the group consisting of copper, nickel and chromium, preferably nickel.
13. The metal-plated product according to claim 10, characterized in that: Wherein the metal-coated article comprises a peel strength greater than 0.4 N / mm measured according to ASTM B533-85.
14. A metal-plated product, characterized in that: include: Metal layer; A thermoplastic article, wherein (i) the metal layer is adhered to at least a portion of a surface of the thermoplastic article, and (ii) the thermoplastic article comprises: a first copolymer in an amount of 30% to 80% by weight of the composition, preferably 45% to 75% by weight of the composition, wherein the first copolymer comprises polymer units derived from a vinyl aromatic monomer and a vinyl nitrile monomer; a rubber modified polymer in an amount of 18% to 50% by weight of the composition, preferably 30% to 45% by weight of the composition; and 2% to 15% by weight of a styrene maleic anhydride (SMA) copolymer, wherein the SMA copolymer comprises a maleic anhydride content of 10% to 30% by weight of the SMA copolymer, preferably 12% to 25% by weight of the SMA copolymer, more preferably 15% to 20% by weight of the SMA copolymer, wherein the SMA copolymer comprises a weight average molecular weight of 5,000 g / mol to 30,000 g / mol, preferably 10,000 g / mol to 25,000 g / mol, more preferably 15,000 g / mol to 20,000 g / mol.
15. The metal-plated product according to claim 14, characterized in that: The metal-plated product includes an automobile or an electrical component.
